2019
DOI: 10.1051/e3sconf/20199904010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Ecotoxicity of Size-fractionated Airborne Particulate Matter

Abstract: Particulate matter (PM) is grouped as coarse, fine, and ultrafine particles (UFPs) with aerodynamic diameters of 2.5 to 10 μm (PM10), <2.5 μm (PM2.5), and <0.1 μm (PM0.1), respectively. The course and fine fractions have been well characterised from numerous aspects, including potential environmental hazard. However, more and more studies are targeted to the UFP fraction, as they bind relatively higher concentrations of potentially toxic materials and they might penetrate through cell biological barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The method of measuring ecotoxicity using photobacterium bioluminescence inhibition bioassay has long been routinely applied and standardized for water and soil research (Water quality, 2007). It had been reported that the Vibrio fischeri EC50 (median effective concentration) significantly correlated to rat and mouse LD50 (the lethal dose for 50 % of the animals tested) values, indicating the reliability of photobacterium-based ecotoxicity as-say (Fort, 1992;Kaiser et al, 1994). Recently, photobacteria have also been often used to assess the ecotoxicity of particulate matter and chemical components in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of measuring ecotoxicity using photobacterium bioluminescence inhibition bioassay has long been routinely applied and standardized for water and soil research (Water quality, 2007). It had been reported that the Vibrio fischeri EC50 (median effective concentration) significantly correlated to rat and mouse LD50 (the lethal dose for 50 % of the animals tested) values, indicating the reliability of photobacterium-based ecotoxicity as-say (Fort, 1992;Kaiser et al, 1994). Recently, photobacteria have also been often used to assess the ecotoxicity of particulate matter and chemical components in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2016) demonstrated that the PM 2.5 components analyzed by Photobacterium Phosphoreum T3 bioassay were ecologically toxic. Eck-Varanka et al (2019) analyzed the ecotoxicity of size-fractionated particles using Vibrio fischeri. Such literature proved the feasibility of the photobacterium-based method in assessing the ecological toxicity of atmospheric particulate matter.…”
Section: Introductionmentioning
confidence: 99%